PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS INKUIRI MENGGUNAKAN 3D PAGEFLIP PROFESSIONAL TEMA 8 KELAS IV SDN 173538 TAMPUBOLON BALIGE - Eva Betty Simanjuntak; Risvi Marliani; Panni Ance Lumbantobing (Universitas Negeri Medan, 2022)
This research was conducted with the aim of developing, knowing the feasibility, and knowing the effectiveness of the inquiry-based Student Worksheet (LKPD) using 3D Pageflip Professional on Theme 8 My Living Area Class IV SDN 173538 Tampubolon Balige. The type of research used in this research is Research and Development (R&D) using the ADDIE research model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques in this study are test and non-test techniques. From the results of the validation carried out by material experts, design experts, and education practitioners, it shows that the inquiry-based Student Worksheet (LKPD) using the professional 3D Pageflip developed is valid. The average percentage of the results of material validation shows 95% in the very feasible category, the results of design validation show 94.4% in the very feasible category, and validation by education practitioners shows 96% in the very feasible category. From the results of the effectiveness test on the learning outcomes of fourth grade students at SDN 173538 Tampubolon Balige at the time of pre-test and post-test, there was an increase. The average pre-test score was 68.7%, while the post-test average was 91.5%. This shows that the students' post-test scores are higher than the pre-test scores.